Maximum speed exposures in Australian rules football: do methods matter? - Dillon, P.; Lovell, R.; Joyce, D.; Norris, D. (Science and Medicine in Football, 2024)
This study compared weekly near-to-maximum speed exposure data when determined via different methods and criteria. Forty-seven professional Australian rules football (AF) players undertook pre-season sprint assessments (PSSA) via 3 × 50 m maximal efforts using 10 Hz GPS over two consecutive seasons. The same technology was used continually during the in-season to identify maximum speeds attained in training and matches. Weekly near-to-maximal speed (MS) exposure counts were aggregated for speeds =80%, =85%, =90% and =95% of their individual maximum for both determination approaches. Weekly near-to-MS exposures was lower (p < 0.0001) when determined from in-season monitoring for =80% (-1.26; CI: -1.58 to -0.93), =85% (-0.78; CI: -0.97 to -0.59), =90% (-0.42; CI: -0.53 to -0.32), and =95% (-0.09; CI: -0.12 to -0.06) versus PSSA, with no effect of playing position (P = 0.161). Although =80% and =85% near-to-maximum speed exposure data was meaningfully influenced by the determination method, the effect was somewhat trivial at higher speed criteria (=90% and =95%) often considered important for performance gains and injury risk reduction purposes. Maximum speed determination methods therefore may be used interchangeably, and discrete sprint assessments may not be necessary for this purpose.